Fish spawning aggregations in the Gulf of Chiriqui, Panamanian Pacific: six years of monitoring - Robles P., Yolani A. (2026)
Introduction: Fish spawning aggregations (FSAs) are temporary concentrations of individuals of the same species that form for the sole purpose of reproducing. Objective: To document the species, times, and localities where FSAs occur in the Gulf of Chiriqui, Panamanian Pacific. Methods: From 2020 to 2025, SCUBA surveys and photographic documentation were conducted to identify FSAs within Coiba National Park (CNP) and the Islas Secas Archipelago (ISA) in the Gulf of Chiriquí. Environmental data, including temperature, salinity, and pH were collected using a YSI EXO2 multiparameter probe, and temperature was continuously recorded with a HOBO Water Temperature Pro v2. Results: The FSAs were recorded for three snapper species (Lutjanus peru, Lutjanus colorado and Lutjanus aratus); one jack (Caranx sexfasciatus); one grouper (Cephalopholis colonus); and one wrasse (Thalassoma lucasanum). Aggregations were observed at Bajo 20, Sacramento, Sueño del Pescador, and Montaña Rusa within CNP, and at Bajo Rizo in ISA. In the latter location, aggregations were recorded for T. lucasanum, C. colonus, and L. colorado. During aggregations, water column stratification was observed, associated with the intrusion of cold-water masses into the gulf, thermocline shoaling, and a decrease in dissolved oxygen concentrations, all correlated with temperature dynamics. Spawning events were most frequently observed in the morning hours. Conclusion: The number of reported species forming FSAs in CNP increased from three to seven, and FSAs were documented for the first time in ISA for three species.